2017
DOI: 10.1021/acsami.7b03298
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aggregation on the Photochemistry of Fullerene Films: Correlating Stability to Triplet Exciton Kinetics

Abstract: The photochemistry and stability of fullerene films is found to be strongly dependent upon film nanomorphology. In particular, PCBM blend films, dispersed with polystyrene, are found to be more susceptible to photobleaching in air than the more aggregated neat films. This enhanced photobleaching correlated with increased oxygen quenching of PCBM triplet states and the appearance of a carbonyl FTIR absorption band indicative of fullerene oxidation, suggesting PCBM photo-oxidation is primarily due to triplet-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 56 publications
8
59
0
Order By: Relevance
“…1(a)). 44 For example, at a lower loading of PC 61 BM, a lower degree of PC 61 BM aggregation in conjunction with a higher yield of triplet states was observed, resulting in more severe photo-oxidation of PC 61 BM. This is consistent with tripletmediated photo-oxidation, analogous to that observed in polymer:fullerene blends via the donor polymer triplets.…”
Section: Photo-oxidation Of Fullerenesmentioning
confidence: 99%
“…1(a)). 44 For example, at a lower loading of PC 61 BM, a lower degree of PC 61 BM aggregation in conjunction with a higher yield of triplet states was observed, resulting in more severe photo-oxidation of PC 61 BM. This is consistent with tripletmediated photo-oxidation, analogous to that observed in polymer:fullerene blends via the donor polymer triplets.…”
Section: Photo-oxidation Of Fullerenesmentioning
confidence: 99%
“…Typically, the small molecules used have been fullerene derivatives such as [6,6]-phenyl-C-61-butyric acid methyl ester (PC 60 BM), [6,6]-phenyl-C-71-butyric acid methyl ester (PC 70 BM), and 1′,1″,4′,4″-tetrahydro-di [1,4]methanonaphthaleno [5,6]fullerene-C 60 (ICBA), achieving efficiencies of 11% [1,2] and lifetimes exceeding several years. Stability issues are also common, with light-induced effects causing strong burn-in degradation, [5,6] poor thermal stability, [7][8][9] and photo-oxidation, [10,11] reducing the viability of using fullerene-based acceptors in commercial modules. An inability to tune the chemical structure inhibits morphological or energetic optimization, to the effect that progress in the field has mostly been driven by the design Nonfullerene acceptors (NFAs) dominate organic photovoltaic (OPV) research due to their promising efficiencies and stabilities.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the photooxidation of the PC 60 BM itself was found to be accelerated by its dispersion in a TQ1 matrix, which Hansson et al 27 assigned to the enhanced absorption range. Interestingly, Speller et al 28 showed a similar acceleration of the PC 60 BM photodegradation when PC 60 BM is dispersed in a transparent non-conjugated polymer (polystyrene) matrix. They also found that the epoxide defects that are formed in the early stages of photo-oxidation, prior to carbonyl formation and cage opening, hamper the electron transport.…”
Section: Introductionmentioning
confidence: 87%